ASUHAN KEBIDANAN PADA BAYI NY ”M” DENGAN ASFIKSIA RINGAN DI BPS SRI RAHMAWATI,. S.ST KELURAHAN TIBOJONG KECAMATAN TANETE RIATTANG TIMUR KABUPATE BONE (Jurnal Suara Kesehatan, 2016)
Midwifery Care for Mrs "M" Infants with Mild Asphyxia at BPS Sri Rahmawati, S.ST. Tibojong Village, Tanete Riattang Timur District, Bone Regency. The aim is to be able to carry out midwifery care for infants with mild asphyxia, to be able to carry out midwifery care data assessments and analysis, formulate diagnoses / actual problems of midwifery care, formulate potential problems, carry out immediate action and collaboration, plan midwifery care measures, carry out midwifery care measures, perform evaluation of midwifery care and carrying out documentation of midwifery care for Mrs. “M” baby with mild asphyxia. The results of this study Diagnosis / actual problems in the baby Mrs. "M", namely a). Term infants, percentage at the back of the head, spontaneous with mild asphyxia. Diagnostic potential in the baby Mrs. "M" is the potential that is the occurrence of asphyxia is. There are no supporting data for immediate action and collaboration with doctors because the baby's condition Mrs. “M” is in a stable state, that is, there are no signs of respiratory distress or hypothermia. The midwifery care measures performed on the baby Mrs. “M” were assessing the condition of the baby after birth, clearing the airway by sucking mucus, drying and wrapping the baby, performing tactile stimulation. The implementation of the action / implementation of midwifery care carried out on the baby Mrs. "M" is in accordance with the plan that the author has compiled and there is no finding any gaps between theory and case study